2020
DOI: 10.31234/osf.io/5b3cn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why is right-wing media consumption associated with lower compliance with COVID-19 measures?

Abstract: Exposure to right-wing media has been shown to relate to lower perceived threat from COVID-19, lower compliance with prophylactic measures against it, and higher incidence of infection and death. What features of right-wing media messages account for these effects? In a preregistered cross-sectional study (N = 554) we test a model that differentiates perceived consequences of two CDC recommendations—washing hands and staying home—for basic human values. People who consumed more right-wing media perceived these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…All study materials, data, and code can be found at https://osf.io/ft4q3. The data that support the findings of this study are openly available in Open Science Framework repository at http://doi.org/10.17605/OSF.IO/ FT4Q3 (Ponizovskiy, Grigoryan, & Hofmann, 2020).…”
Section: Conflict Of Interestsupporting
confidence: 64%
See 2 more Smart Citations
“…All study materials, data, and code can be found at https://osf.io/ft4q3. The data that support the findings of this study are openly available in Open Science Framework repository at http://doi.org/10.17605/OSF.IO/ FT4Q3 (Ponizovskiy, Grigoryan, & Hofmann, 2020).…”
Section: Conflict Of Interestsupporting
confidence: 64%
“…The two factors correlated positively ( r = .53, p < .001). See Online Supplement for details (Ponizovskiy et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this possibility, geo-tracking data show that counties that support Trump and consume more conservative news sources tend to engage in less social distancing, even with stay-at-home orders in effect (Gollwitzer et al, 2020). Similarly, exposure to right-wing media decreases compliance with preventative behaviors such as hand-washing and staying home (Ponizovskiy et al, 2020), as does lower consumption of liberal media (Samore et al, 2020). Although not experimental, this emerging work suggests that lower rates of social distancing among conservatives might be driven, at least in part, by exposure to sources that breed mistrust in the science around COVID-19.…”
Section: Ideology and Trust In Sciencementioning
confidence: 99%
“…Numerous studies have shown that media coverage during the pandemic has likely influenced the perceptions and attitudes of the public toward a wide range of issues, including food consumption, social distancing protocols, vaccines, travel plans, and other socio-economic activities (Chemli et al 2020;Gozzi et al 2020;Helm 2020). However, it has also been demonstrated that the information disseminated by media outlets does not always result in the greater good for society and may even exacerbate perverse situations related to the pandemic, such as questioning the value of adhering to social distancing and other recommended public health guidelines, thereby promoting the spread of the virus and potentially increasing the number of fatalities that have occurred (Ponizovskiy et al 2020).…”
Section: Introductionmentioning
confidence: 99%